دراسة العوامل التصميمية المؤثرة في عملية المعالجة البيولوجية بالتهوية المديدة لمياه الصرف الصحي للمشافي - جناد هيثم; صبوح حسام; عطية آمال (Latakia University Journal -Engineering Sciences Series, 2019)
ازدادت أهمية معالجة مياه الصرف الصحي الناتجة من المشافي، بسبب تأثيرها السلبي في البيئة والإنسان. ولقد أثبتت عملية التهوية المديدة لمياه الصرف الصحي للمشافي فعاليتها في تخفيض تركيز الـ BOD5 إلى الحد الذي يسمح بالتخلص منها بيئياً بشكل سليم. يهدف هذا البحث إلى تحديد القيم التصميمية للعوامل المؤثرة في عملية المعالجة البيولوجية بالتهوية المديدة لمياه الصرف الصحي للمشافي ( بانياس و الحفة ) والمأخوذة بالحسبان كزمن التهوية وشدة التهوية، للاستفادة منها في تصميم محطة معالجة بيولوجية بالتهوية المديدة لهذه المشافي. أظهرت نتائج البحث فعالية عملية التهوية المديدة في تخفيض تركيز الـ BOD5، وارتبط ذلك بالعوامل الأخرى كزمن التهوية وشدة التهوية. ويمكن من خلال التحكم بالعوامل المذكورة الوصول إلى الحدود المثلى لإزالة التلوث العضوي والمعبر عنه بقيمة الـ BOD5. The importance of hospitals wastewater treatment increased, because of their negative impact on the environment and humans. The extended aeration of hospitals wastewater had proved an effective system in reducing the concentration of BOD5. The research aims to study the main factors affecting the process of biological treatment by extended aeration of hospitals wastewater ( Banias and Hafeh ), which is taken into account as the time and intensity of aeration to be used in design biological treatment system by extended aeration for hospitals. Results showed the efficiency of extended aeration system in reducing the concentration of BOD5 with relation to other factors, such as the time and intensity aeration. By controlling the studied factors, the optimum condition of removing organic pollution BOD5 should be achieved.